121k views
5 votes
What is the inverse of g(n) = -5n - 5


User Ood
by
5.1k points

2 Answers

6 votes

Answer:

-n - 5

f^-1(x) = 5 or (-n - 5)/5

Explanation:

g(n) = -5n - 5

RS | SR

Replace: y = -5n - 5

Switch n & y: n = -5n - 5

Solve for y:

n = -5y - 5. Isolate y

+5 +5

-1(n + 5) = (-5y) -1 Multiply each side by

-1 so that y isn't

negative.

-n - 5 = 5y Divide 5 on each side. 5

5 5 comes from 5y

-n - 5

y = 5

Replace y with f^-1(x):

-n - 5

f^-1(x) = 5

User Powell Quiring
by
5.4k points
5 votes

y=-5n-5

switch the signs to find inverse and solve for y

n=5y-5

n+5=5y

divide by 5

1/5n+1=y

that's your inverse my dude

User Marcus Hughes
by
5.2k points